Enhancing balance and auditory function in bilateral vestibulopathy through otolithic vestibular stimulation: insights from a pilot study on cochlea-vestibular implant efficacy - Ramos-de-Miguel, Ángel; Sluydts, Morgana; Falcón, Juan Carlos; Manrique-Huarte, Raquel; Rodriguez, Isaura; Zarowski, Andrzej; Barbara, Maurizio; Manrique, Manuel; Borkoski, Silvia; Lorente, Joan; Leblanc, Marc; Rambault, Antonin; et al. (Frontiers in Neurology, 2025)
IntroductionThis study evaluates cochleovestibular implants (CVI) for improving auditory and vestibular function in patients with bilateral vestibulopathy and severe-to-profound hearing loss. CVI uniquely combines auditory and vestibular stimulation, offering a potential solution for dual impairments in hearing and balance.MethodsTen patients underwent CVI implantation. Auditory function was assessed with pure-tone audiometry (PTA) and speech recognition at baseline, 3, and 9 months post-implantation. Vestibular function was measured using the Dynamic Gait Index (DGI), Sensory Organization Test (SOT), posturography, and the Dizziness Handicap Inventory (DHI). Placebo-controlled tests verified cochleovestibular stimulation specificity.ResultsAuditory outcomes showed PTA improvements from 78 dB HL preoperatively to 34 dB HL at 3 months and 36 dB HL at 9 months, alongside speech recognition gains. Vestibular improvements included significant DGI (p < 0.05) and SOT score increases (33% to 68%, p < 0.05). DHI scores reflected reduced dizziness-related disability. Residual balance gains after device deactivation suggest neural adaptation, and placebo tests confirmed cochleovestibular stimulation specificity.DiscussionCVI effectively restores auditory and vestibular function, with improvements in hearing, balance, and quality of life. Neural plasticity likely supports long-term benefits. Future research should refine device design and stimulation protocols to enhance outcomes further.